Engineering dithiobenzoic acid lactone-decorated Si-rhodamine as a highly selective near-infrared HOCl fluorescent probe for imaging drug-induced acute nephrotoxicity. Issue 73 (23rd August 2019) - Wang, Jinping; Cheng, Dan; Zhu, Longmin; Wang, Peng; Liu, Hong-Wen; Chen, Mei; Yuan, Lin; Zhang, Xiao-Bing
Abstract : A NIR fluorescent probe based on Si-rhodamine dithiobenzoic acid lactone was used to selectively visualize HOCl during GEN-induced nephrotoxicity for the first time. Abstract : A highly selective lysosome-targeting NIR fluorescent probe (Lyso-SiR-2S ) for HOCl was constructed based on Si-rhodamine B spirodithiolactone. This probe was very effectively employed to sense HOCl produced in various living cells and to visualize fluctuations of endogenous HOCl resulting from GEN-induced acute kidney injury in vivo for the first time.